(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2009)
Dataon19 speciesofaphyllophoroidfungiaregiven(Antrodiellafragrans, Atheliaepiphylla, Ceraceomycessulphurinus, Clavariadelphustruncatus, Dendrothelealliacea, Granulobasidiumvellereum, Hyphodermamedioburiense, Hypochniciumwakefieldiae, Peniophoralilacea, Perenniporianarymica, Phanerochaetecalotricha, P.subquercina, Phellinushippophaeicola, Radulomycesrickii, Tomentellacinereoumbrina, T. umbrinospora, Tubulicrinissubulatus, Vuilleminiaalni, V.coryli). These species are reported for Ukraine for the first time.